The Association Between Maternal Nutritional Status and Intrauterine Growth Restriction: A Literature Review - Nurul Azizah; M Hamsah; Nugraha Utama Pelupessy (CV. Global Health Publication, 2026)
Background: Intrauterine Growth Restriction (IUGR) is a pathological condition in which the fetus fails to achieve its genetically determined growth potential and remains a major contributor to perinatal morbidity and mortality. Maternal nutritional status is a key modifiable factor influencing placental function and fetal growth. Aim: This study aimed to analyse the association between maternal nutritional status and the occurrence of intrauterine growth restriction. Methods: This study employed a descriptive-analytic literature review approach. Scientific articles published within the last ten years were reviewed. Maternal nutritional indicators analysed included pre-pregnancy body mass index (BMI), mid-upper arm circumference (MUAC), gestational weight gain, haemoglobin levels, and macro- and micronutrient intake. Results: Poor maternal nutritional status, including low BMI, MUAC <23.5 cm, inadequate gestational weight gain, anaemia, and micronutrient deficiencies, was consistently associated with an increased risk of IUGR. These conditions were linked to placental insufficiency, reduced uteroplacental perfusion, and chronic fetal hypoxia. Conclusion: Maternal nutritional status is significantly associated with intrauterine growth restriction. Optimising maternal nutrition before and during pregnancy is essential to prevent IUGR and improve perinatal outcomes.